Analysis of the Utilization of Augmented Reality (AR) Technology in Interactive Science Learning in Schools - Rustiyana Rustiyana (Technologia Journal, 2025)
This study aims to analyze the use of Augmented Reality (AR) technology to support interactive science learning in schools. The research method used is a qualitative approach with a case study design, involving direct classroom observation, in-depth interviews with teachers and students, and documentation of learning activities. The results show that the use of AR can increase students' interest in learning and understanding of abstract concepts in science. AR also encourages more interactive and participatory learning. The role of teachers shifts to that of facilitators who need to master technological tools and design innovative learning strategies. However, the implementation of AR in schools still faces obstacles such as limited infrastructure and educators' digital competencies. These findings provide important insights into the potential and challenges of AR integration in education, and serve as a basis for policy development and teacher training to encourage digital transformation in science learning.